Pengaruh Perbandingan Tepung Singkong Dan Puree Daun Kelor Terhadap Karakteristik Farfalle Basah - Eka Putra Sentana, I Putu; Timur Ina, Putu; Mayun Permana, I Dewa Gede (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 1 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i01.p12, 2021)
The purpose of this research were to know the comparison effect of cassava flour and puree of moringa leaves on the characteristics of wet farfalle and to know the right comparison on the best characteristics of wet farfalle.The experimental design used in this research was a completely randomized design (CRD) with comparison treatment of cassava flour and puree of moringa leaves consisting of 6 level of treatment namely 95%:5%; 90%:10%; 85%:15%; 80%:20%; 75%:25%; 70%:30%. All treatments were repeated three times so that there were obtained 18 experimental units. The data obtained were analiyzed by Analysis of Variance and if the treatment had significant effect then followed by Duncan Multiple Range Test. The result showed that the comparation of cassava flour and puree of moringa leaves had significant effect on the water content, vitamin C, chlorophyll total, antioxidant activity, color preference (scoring test) and overall acceptance (hedonic test) of wet farfalle. Comparison of 70 % cassava flour and 30 % puree of moringa leaves had the best characteristics with water content of 58.62%, vitamin C of 2.57 mg.AAE/g, chlorophyll total of 9.19 mg/100g, antioxidant activity of 72.90%, and value IC 50 of 40,283 ppm, dark green color and rather liked, aroma rather liked, flavour, texture and overall acceptance liked.